(untitled) (The Pakistan Development Review, 2005)
The issue of whether public investment crowds out or crowds in private investment has received considerable attention in the economic literature. Most of the empirical studies that examined the long run stable association between public and private investment have focused on examining this relationship for the developed countries with very little attention on the developing countries. The empirical results of these studies, however, are highly controversial. The existing empirical studies in this area can be divided into three categories. The studies in the first category including Barro (1974), Kormendi (1983), and Feldstein (1982) have examined the empirical implications of the Ricardian equivalence hypothesis (REH). The empirical results of most of the studies in this category were supportive of the REH. Seater (1993) argues that good empirical studies generally provide evidence in support of the REH; however, some studies refute it owing to the lake of econometric accuracy.